HEPATOCELLULAR CARCINOMA (HCC) AND DIAGNOSTIC SIGNIFICANCE OF α-FETOPROTEIN (AFP) - Baig, Jawed Altaf; Alam, Junaid Mahmood; Mahmood, Syed Riaz; Baig, Muhammad; Shaheen, Rabia; Sultana, Ishrat; Waheed, Abdul (Journal of Ayub Medical College Abbottabad, 2009)
Background: Alpha-fetoprotein (α-fetoprotein, AFP) is a Glycoprotein, belonging to the intriguing class of onco-development protein. Generally designated as tumour marker, AFP is recognized as an important blood component, having specific diagnostic utilities Elevation of its level up to pathological range in adults correlate with the appearance of several malignant and chronic conditions, such as hepatocellular carcinoma (HCC) and chronic liver disease, respectively. Methods: To evaluate the diagnostic significance of AFP in HCC, a study was carried out for a period of two years (Jan 2004 to Dec 2005) A brief history of Patients was taken with clinical symptoms and signs and initial diagnosis. Patients admitted in wards or visiting OPDs with diagnosis or suspicions of HCC and additional conditions of Chronic Liver disease (CLDs), hepatitis C (HCV) and hepatitis B viral (HBV) infections, were selected and classified according to gender. When confirmed, their HCC status was evaluated and classified according to clinical condition. Results: In 1012 adults including, males 762 (75.3%) and females 250 (24.7%) patients suspected of or diagnosed with HCC and presence of HBV and HCV infections. Out of 480 males, who depicted elevated AFP levels, 39 (8.13%) were diagnosed with HCC. Similarly, 7 (5.34%) females out of 131 with elevated levels of AFP were diagnosed with HCC. Mean elevated AFP levels in all HCC patients were, 421ï‚±59 µg/ml (range 157-4019 µg/ml) in males and 163ï‚±32 µg/ml (range 101-2341 µg/ml) in females. In males, the overall estimated mean AFP elevated values were analysed to be 514 µg/ml (range 67-4019±59 µg/ml,), whereas in females it was 396±42 µg/ml (range 21-2341 µg/ml). It was also noted that 43 (8.96%) males and 7 (5.34%) female patients, exhibited elevated levels of AFP, however, found negative for HCV and HBV infections. Conclusion: It is concluded that AFP is a significant markers for Hepatocellular carcinoma, helpful in assessing problems in management of HCC and monitoring treatment regiments. In addition, AFP is also an indicator of HCC risks mostly in patients with cirrhosis and HCV/HBV infections Keywords: AFP, Hepatocellular carcinoma HCC, Hepatitis infections HCV, HBV